Satuan Lingual yang Mengandung Pronomina Persona Ketiga pada Teks Terjemahan Hadis Buchori-Muslim yang Mengandung Etika Berbahasa - Reistanti, Agustina Putri (2016)
This research has three purposes. The first is to describe the hierarchy of lingual unit that contains third personal pronouns in the text of Buchori-Muslim Hadith translation which contains language ethics. The second is to describe the functions filled by lingual unit that contains third personal pronouns in the text of Buchori Muslim Hadith translation which contains language ethics. The third is to describe roles which fill the lingual unit that contains third personal pronouns in the text of Buchori Muslim Hadith translation which contains language ethics. Data collection method of this research is observation and note taking method. The method of data analysis used in this research is padan referential method. The results of the research show that, firstly, the hierarchy of lingual unit containing PP3 in the hadith translation text such words and phrases. Lingual unit of word categorized nouns are dia, ia, beliau, mereka. The lingual unit of word has noun category and the lingual unit of phrases has category noun phrase, prepositional phrase, numeralia phrase and attributive phrase. Secondly, the functions filled by the lingual unit containing third personal pronoun in the hadith translation text are: (1) the function of subject, (2) predicate, (3) object, (4) complement, and (5) adverbial, (6) subject attributes, and (7) object attributes. Thirdly, the roles filled by the lingual unit that contains third personal pronouns are: (1) the role of patient, (2) the role of origin, (3) the role of existance, (4) the role of tool, (5) the role of designation, (6) the role of goals, (7) the role of experience, (8) the role of place, (9) the role of participant, and (10) the of attributive, (11) the role of described, (12) the role of actors, (13) the role of recipient, (14) the role of known.